Meager Perception of Preconception Care Among Women Desiring Pregnancy in Rural Areas: A Qualitative Study Using Focus Group Discussions - Doke, Prakash Prabhakarrao; Gothankar, Jayashree Sachin; Pore, Prasad Dnyandeo; Palkar, Sonali Hemant; Chutke, Amruta Paresh; Patil, Archana Vasantrao; Deshpande, Aniruddha Vinayakrao; Bhuyan, Khanindra Kumar; Karnataki, Madhusudan Vaman; Shrotri, Aparna Nishikant (Frontiers in Public Health, 2021)
Background: India has the second-highest number of under-five deaths in any country in the world. WHO and the Government of India recommended the rollout of preconception care (PCC) to reduce maternal and child mortality. However, very few countries, including India, have started a comprehensive package of PCC services. It implies that women, mainly from rural and tribal areas, are not aware of PCC. PCC has been rolled out through the government health system in two blocks of Nashik district in Maharashtra state, India, among all women who desire to be pregnant within 1 year. This project is the first of its kind in India. To assess basic perceptions, knowledge, and behavior of women on PCC before the implementation of the project, focus group discussions (FGDs) were carried out. The authors think that the finding may help to develop strategies for behavioral change communication. Methods: From each of the four blocks, two villages having subcenter were selected for conducting FGD. A house-to-house survey was conducted by Accredited Social Health Activist (ASHA) to enlist women who desire a baby in 1 year and invite them to subcenter for FGDs, which were conducted in June 2018. Results: A total of 76 women having a mean age of 23.97 years participated in the FGDs. Most of them (46.05%) had completed 10 years of education. About 50% of pregnancies were planned. The decision about the timing of the first pregnancy is influenced by the mother-in-law. Women knew that they should not conceive before 20 years of age, and their suboptimal weight may have an adverse impact on the health of the newborn. There are many myths about food like “hot and cold foods” and “forbidden food” etc. Women had some knowledge about the adverse effects of tobacco and alcohol; very few consumed these. Most of them did not practice behaviors or accessed services related to PCC. Conclusions: Women neither have the knowledge nor adopt behaviors or accessed services related to PCC. Roll out of PCC among them may help in further reduction of maternal and neonatal morbidity and mortality in India.